El The power is nourished by dogmas. The appropriation in the work of Herman Braun-Vega - Guerrero Zegarra, María Alexandra (2021)
The purpose of this article is to demonstrate, within the visual arts, the role of appropriations as a principle of articulation in the work of the Peruvian plastic artist Herman Braun-Vega, through the elements and  characters taken by the artist from History of Western Art. The aesthetic and ideological proposals of the work are analyzed of the work Power is nourished by dogmas (Velásquez [sic], Huamán Poma de Ayala, El Greco) (2006). It is concluded that the appropriation of the image makes a new meaning in the work, while itis recontextualized and reinterpreted, because the appropriations in the work of this artist has the intention of make a rearticulation of the memory (individual, sociopolitical and historical). These images that are appropriations were evidenced through the visual narrative and the function of the political and religious discourse that is contained in them.